Indigenous Television for the Majority: Analyzing NRK Sapmi's Muitte Mu (Remember Me). (July 2021) - Sand, Stine Agnete
This article asks, "How can indigenous media fulfill its obligations toward the indigenous population while also connecting with the majority?" In the entertainment television series Muitte mu, produced by the indigenous public service broadcaster NRK Sápmi in Norway, famous Norwegian artists learn to joik, a Sámi form of music. Muitte mu triggered a discussion concerning cultural appropriation and commercialization, as well as the traditionalist versus pragmatic and interethnic views of indigenous cultural expressions. One of NRK Sápmi's goals is to share content about the Sámi, and, in a market-oriented media environment, the series uses Sámi iconography and celebrities to fulfill this goal. However, this approach does not necessarily resonate with its main obligation, which is to provide programming for the Sámi people. What is at stake in these debates are the credibility, relevance, and legitimacy of NRK Sápmi, all of which depend upon the recognition of the Sámi themselves.